Review the Role of the Transparency Commitment of Human Resource Practices in the Employee’s Satisfaction in Banking Sector - Mozael, Bassam Mohsin; Samsudin, Dr. Norsamsinarbinti (International Journal of English Literature and Social Sciences (IJELS), 2019)
The services in the banks are performed by the employees, and these services should be conducted affectively. The Bank should assure the employees satisfaction in order to enhance the employees' engagement level and motivate the employees to do their best in the working environment. The economic benefits of human resource practices (such as promotions and rewards) play important role in motivate the employees in the working environment through satisfy their extrinsic needs. The main challenge of HRP management is the employees' trust of leaders toward these practices in the organization. This paper aims to reviews the role of HRP manages in the employees' satisfaction in the bank. The review of literature is conducted to address the main aim of this paper. The paper result indicates that in order to enhance the level of employees' satisfaction and working engagement, the leaders should provide effective economic benefits of HRP, the HRP policies should transparent and clear for the employees, and the leaders must honest in apply the HRP policies as real actions in working environment. A conceptual model is suggested to fill the research gap, and the contribution of the suggested model is the presentation of various dimensions of HRP management in the context of employees' satisfaction.